The Implementation of Education Insurance: A Case Study on Takaful Keluarga Insurance - Nasrulloh Nasrulloh; Badrul Mutaqqin (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
Education insurance is an insurance product that guarantees the cost of education for children up to the higher education level. The insured party or the customer is required to pay an amount when the contract is completed according to the agreement of both parties. In practice, education insurance is a combination of the benefits of education funds as well as life insurance. But in fact, insurance participants complained about the procedure for paying education insurance claims. The difficulty of claiming requirements and unclear claims submission processes. This research uses a qualitative research method with a descriptive approach through field research, observation or direct observation, interviews at Surabaya Takaful Keluarga Insurance. The findings show that participants can claim education funds from full-time products according to the time written in the policy book. The Takaful Keluarga Insurance Company provides concessions for policyholders to submit claims one year before the stipulated time as long as there are sufficient savings funds. The implementation of full-blown products in terms of the claim procedure and benefits obtained is following the MUI DSN Fatwa No. 53/DSN-MUI/III/2006 and No. 21/DSN-MUI/ X/2001